Metabolic pathways and intracellular trafficking of gangliosides - Daniotti, Jose Luis (2011)
Gangliosides constitute a large and heterogeneous family ofacidic glycosphingolipids that contain one or more sialic acid residuesand are expressed in nearly all vertebrate cells. Their denovo synthesis starts at the endoplasmic reticulum and is continuedby a combination of glycosyltransferase activities at the Golgicomplex, followed by vesicular delivery to the plasma membrane.At the cell surface, gangliosides participate in a variety of physiologicalas well as pathological processes. The cloning of genes formost of the glycosyltransferases responsible for ganglioside biosynthesishas produced a better understanding of the cellular andmolecular basis of the ganglioside metabolism. In addition, theability to delete groups of glycosphingolipid structures in micehas been enormously important in determining their physiologicalroles. Recently, a number of enzymes for ganglioside anabolismand catabolism have been shown to be associated with the plasmamembrane, which might contribute to modulate local glycolipidcomposition, and consequently, the cell function.